2023
DOI: 10.3389/frtra.2023.1178452
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the liver transplant candidate

Abstract: The first successful human liver transplant (LT) was done over 60 years ago; since the early pioneering days, this procedure has become a routine treatment with excellent outcomes for the great majority of recipients. Over the last six decades, indications have evolved. Use of LT for hepatic malignancy is becoming less common as factors that define a successful outcome are being increasingly defined, and alternative therapeutic options become available. Both Hepatitis B and C virus associated liver disease are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 77 publications
0
0
0
Order By: Relevance
“…Interestingly, the data over the last 2 decades has argued otherwise, and patients with SUDs are now increasingly being considered for transplant. In the 2000s, hepatitis C was the leading indication for LT. Today, alcohol-associated liver disease (ALD) is the leading indication [1,2] This paper will review the LT outcomes for patients with alcohol use disorder (AUD) and opioid use disorder (OUD).There has been robust data over the last 2 decades demonstrating that rates of survival, adherence, and acute rejection are generally comparable between patients who receive LT for ALD and for non alcoholassociated liver disease. In a 2018 review, Rogal et al found that survival rates posttransplant were comparable and sometimes even better in patients with ALD compared to patients receiving transplants for viral or autoimmune illnesses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the data over the last 2 decades has argued otherwise, and patients with SUDs are now increasingly being considered for transplant. In the 2000s, hepatitis C was the leading indication for LT. Today, alcohol-associated liver disease (ALD) is the leading indication [1,2] This paper will review the LT outcomes for patients with alcohol use disorder (AUD) and opioid use disorder (OUD).There has been robust data over the last 2 decades demonstrating that rates of survival, adherence, and acute rejection are generally comparable between patients who receive LT for ALD and for non alcoholassociated liver disease. In a 2018 review, Rogal et al found that survival rates posttransplant were comparable and sometimes even better in patients with ALD compared to patients receiving transplants for viral or autoimmune illnesses.…”
mentioning
confidence: 99%
“…Interestingly, the data over the last 2 decades has argued otherwise, and patients with SUDs are now increasingly being considered for transplant. In the 2000s, hepatitis C was the leading indication for LT. Today, alcohol-associated liver disease (ALD) is the leading indication [1,2] This paper will review the LT outcomes for patients with alcohol use disorder (AUD) and opioid use disorder (OUD).…”
mentioning
confidence: 99%